Astemizole Synergizes Calcitriol Antiproliferative Activity by Inhibiting CYP24A1 and Upregulating VDR: A Novel Approach for Breast Cancer Therapy - García-Quiroz, Janice; García-Becerra, Rocío; Barrera, David; Santos, Nancy; Avila, Euclides; Ordaz-Rosado, David; Rivas-Suárez, Mariana; Halhali, Ali; Rodríguez, Pamela; Gamboa-Domínguez, Armando; Medina-Franco, Heriberto; Camacho, Javier; et al. (PLOS ONE, 2012)
Background Calcitriol antiproliferative effects include inhibition of the oncogenic ether-à-go-go-1 potassium channel (Eag1) expression, which is necessary for cell cycle progression and tumorigenesis. Astemizole, a new promising antineoplastic drug, targets Eag1 by blocking ion currents. Herein, we characterized the interaction between calcitriol and astemizole as well as their conjoint antiproliferative action in SUM-229PE, T-47D and primary tumor-derived breast cancer cells. Methodology/Principal Findings Molecular markers were studied by immunocytochemistry, Western blot and real time PCR. Inhibitory concentrations were determined by dose-response curves and metabolic activity assays. At clinically achievable drug concentrations, synergistic antiproliferative interaction was observed between calcitriol and astemizole, as calculated by combination index analysis (CI <1). Astemizole significantly enhanced calcitriol’s growth-inhibitory effects (3–11 folds, P<0.01). Mean IC20 values were 1.82±2.41 nM and 1.62±0.75 µM; for calcitriol (in estrogen receptor negative cells) and astemizole, respectively. Real time PCR showed that both drugs alone downregulated, while simultaneous treatment further reduced Ki-67 and Eag1 gene expression (P<0.05). Astemizole inhibited basal and calcitriol-induced CYP24A1 and CYP3A4 mRNA expression (cytochromes involved in calcitriol and astemizole degradation) in breast and hepatoma cancer cells, respectively, while upregulated vitamin D receptor (VDR) expression. Conclusions/Significance Astemizole synergized calcitriol antiproliferative effects by downregulating CYP24A1, upregulating VDR and targeting Eag1. This study provides insight into the molecular mechanisms involved in astemizole-calcitriol combined antineoplastic effect, offering scientific support to test both compounds in combination in further preclinical and clinical studies of neoplasms expressing VDR and Eag1. VDR-negative tumors might also be sensitized to calcitriol antineoplastic effects by the use of astemizole. Herein we suggest a novel combined adjuvant therapy for the management of VDR/Eag1-expressing breast cancer tumors. Since astemizole improves calcitriol bioavailability and activity, decreased calcitriol dosing is advised for conjoint administration.